World War II in Andreï Makine's historiographic metafiction : "No one is forgotten, nothing is forgotten" - Duffy, Helena (Faux titre, 2018)
"Can it be ever possible to write about war in a work of fiction? asks a protagonist of one of Makine's strongly metafictional and intensely historical novels. Helena Duffy's World War II in Andreï Makine's Historiographic Metafiction redirects this question at the Franco-Russian author's fiction itself by investigating its portrayal of Soviet involvement in the struggle against Hitler. To write back into the history of the Great Fatherland War its unmourned victims -- invalids, Jews, POWs, women or starving Leningraders -- is the self-acknowledged ambition of a novelist committed to the postmodern empowerment of those hitherto silenced by dominant historiographies. Whether Makine succeeds at giving voice to those whose suffering jarred with the triumphalist narrative of the war concocted by Soviet authorities is the central concern of Duffy's book"--